Revolutionizing Breast Imaging: Artificial Intelligence’s Role in Precisely Differentiating Benign from Malignant Lesions (Canadian Oncology Today, 2024)
Recent advancements in artificial intelligence (AI) have leveraged computer science with large datasets to improve predictive and classification capabilities, which are crucial for problem‑solving in radiology. Machine Learning (ML), the driving force behind AI’s effectiveness, harnesses computational models and algorithms to analyze raw data for classification and prediction tasks. AI utilizes a multi-layered network of interconnected nodes emulating the intricate neuronal structure of the human brain. These include an input layer that initially receives data, a hidden layer that discerns data patterns, and an output layer that presents the results of the processed data.